1991
DOI: 10.1080/02652039109373950
|View full text |Cite
|
Sign up to set email alerts
|

Sensory analysis of polystyrene packaging material taint in cocoa powder for drinks and chocolate flakes

Abstract: Polystyrene packaging material taint was sensorily evaluated in cocoa powder for drinks and chocolate flakes using short-cut signal detection measures on differences between control and test samples and on recognition of styrene. No differences were observed in cocoa powder for drinks and plain chocolate flakes treated with 0.5 dm2 polystyrene of 1 mm thickness. However, differences were detected in milk chocolate flakes and plain chocolate flakes, which were in contact with a larger area or thicker polystyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Figure 3 presents the scores of sensory attributes assessed with and without nose-clips for French beans stored at different conditions. Comparison of Figs 3A and 3B reveals that the use of nose-clips diminished the scores for sensory attributes in general, which is in agreement with previous studies (Linssen et al 1991;Van Ruth et al 1995a). Apparently, volatile compounds contribute to the flavour of rehydrated French beans.…”
Section: Resultssupporting
confidence: 91%
“…Figure 3 presents the scores of sensory attributes assessed with and without nose-clips for French beans stored at different conditions. Comparison of Figs 3A and 3B reveals that the use of nose-clips diminished the scores for sensory attributes in general, which is in agreement with previous studies (Linssen et al 1991;Van Ruth et al 1995a). Apparently, volatile compounds contribute to the flavour of rehydrated French beans.…”
Section: Resultssupporting
confidence: 91%
“…A more recent investigation into the sensory effects of styrene monomer migrating from polystyrene plastics into cocoa powder for drinks and chocolate flakes, was carried out in The Netherlands (Linssen et al, 1991). The results obtained with cocoa powder and extrapolated for the cocoa drinks, confirmed the predictions of Ramshaw (1984) that migration of the styrene monomer is higher in products with high fat content.…”
Section: Plastics Packagingsupporting
confidence: 81%
“…Another reason could be that the assessors in the present study were not acquainted with the taste of styrene. A former study has shown that detection was more difficult than recognition of styrene in chocolate products (Linssen et al 1991).…”
Section: Resultsmentioning
confidence: 99%